INSURED PERSON AND INSURED RISK IN LIABILITY INSURANCE FOR DAMAGES CAUSED BY THE INFLUENCE ON THE ENVIRONMENT - Marjanski, Vladimir; Fišer Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Liability insurance for environmental damages has been existing in some European countries and in the United States for more than a hundred years. In the Republic of Serbia, however, this type of insurance is still quite underdeveloped. The subject matter of this paper is the analysis of, according to the authors’ opinion, two most important issues of liability insurance for damages arising out of the harmful influence on the environment. The first question is who is capable of being an insured person in this type of insurance and the second one, what represents an insured risk and how it should be described when formulating an insurance policy. In the paper these two aspects have been analyzed according to the applicable laws of the Republic of Serbia, relevant international documents and general and specific terms and conditions of domestic and foreign insurance companies.